New Zealand : 2012 Article IV Consultation: Staff Report; Staff Supplement; Public Information Notice. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The New Zealand economy continues to grow at a modest pace. The 2012 Article IV Consultation reports that domestic demand has remained soft as households and businesses continue to deleverage amid a weak housing market and an uncertain outlook. Executive Directors endorse that output growth should pick up somewhat in 2012 as earthquake reconstruction spending is expected to gain pace. High household debt is likely to weigh on the growth of private consumption as households will need to save to strengthen their balance sheets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet